Racial and Ethnic Disparities in the Use of High-Volume Hospitals - Bradford H. Gray; Mark Schlesinger; Shannon Mitchell Siegfried; Emily Horowitz (SAGE Publishing, 2009)
Differences in the source of care could contribute to racial and ethnic disparities in health status. This study looks at a major metropolitan area and examines racial and ethnic differences in the use of high-volume hospitals for 17 services for which there is a documented positive volume-outcome relationship. Focusing on the hospitalizations of New York City area residents in the periods 1995-1996 and 2001-2002, we found, after controlling for socioeconomic characteristics, insurance coverage, proximity of residence to a high-volume hospital, and paths to hospitalization, that minority patients were significantly less likely than whites to be treated at high-volume hospitals for most volume-sensitive services. The largest disparities were between blacks and whites for cancer surgeries and cardiovascular procedures.